Development Of Hiro Card Media on Mathematics Lessons For Roman Numbers In Class Iv Sd Negeri Sempu 2 City Of Serang: Research and Development On Fourth Grade at SDN Sempu 2 Serang - Siahaan, Fenny Aprianty Siahaan; Michel, Joseph (Jurnal Gentala Pendidikan Dasar, 2023)
This study aims to: 1) determine the process of developing Hiro Card learning media in mathematics, 2) determine the feasibility of Hiro card learning media in mathematics. This research uses Research and Development (R&D) research using a 4D development model with stages, namely define, design, development, desiminate. This learning media goes through the stages of media validation test, material validation test, and product testing. The subjects of this research are the fourth grade students of SD Negeri Sempu 2 Serang City as many as 25 students. Based on the results of the study, the average validation of media experts was 90 with the "very feasible" category, material expert validation was 80 in the "very feasible" category, student responses were 92% in the "very good" category. Thus, it can be concluded that the Hiro Card learning media is declared suitable for use as a learning medium, especially in mathematics.